Ability of TyG Index as a Marker of Insulin Resistance in Argentinean School Children - Hirschler, Valeria; Molinari, Claudia; Edit, Scaiola; Miorin, Cecilia; Bocco, Patricia; Guntsche, Zelmira; Lapertosa, Silvia; Gonzalez, Claudio D. (Frontiers in Pediatrics, 2022)
Objective: To determine if the triglycerides and glucose index (TyG) can be used as a marker for insulin resistance (IR) in Argentinean schoolchildren according to age and sex. Methods: Anthropometric data, blood glucose levels, lipid profiles, and insulin levels were measured. The TyG index was defined by Ln [fasting triglyceride (mg/dL)* fasting glucose (mg/dL)/2). A comparison of the ability of TyG to identify children with IR was performed using receiver operating characteristic (ROC) curves and the area under the ROC (AUROC) curve. IR was defined as HOMA-IR>III quartile. Results: 915 (528, 57.7% males) apparently healthy schoolchildren, aged 9.3 ± 2.2, were evaluated. The AUROC using the HOMA-IR>III quartile as the dichotomous variable showed that TyG was a fair marker to identify IR (0.65, 95% CI 0.61-0.69; p<0.01). There was a significantly higher TyG AUROC in males (0.69, 95% CI 0.63-0.75; p<001) than in females (0.60, 95% CI 0.54-0.66; p<0.01). When children were divided according to age into two groups (5.0–9.9 and 10.0–14.9-year-olds); younger children (0.64, 95% CI 0.58-0.69; p<0.011) and older children (0.62, 95% CI 0.55-0.68; p=0.01) had a similar and fair AUROC. However, when children were divided by age and sex, females older than ten had a non-significant AUROC (0.53, 95% CI 0.42-0.63; p=0.61). The TyG index compared with HOMA-IR had low sensitivity and specificity, ranging from 0.62 to 0.56. Conclusion: The TyG index had a fair AUROC with low sensitivity and specificity, indicating poor discrimination in identifying IR in apparently healthy Argentinean children. The ability to use TyG for screening purposes seems limited in Argentinean schoolchildren.